Microstructural dependence of the fracture toughness of metallic thin films: A bulge test and atomistic simulation study on single-crystalline and polycrystalline silver films. Issue 20 (28th October 2019) - Preiß, Eva I.; Lyu, Hao; Liebig, Jan P.; Richter, Gunther; Gannott, Florentina; Gruber, Patric A.; Göken, Mathias; Bitzek, Erik; Merle, Benoit
Abstract: Abstract : The microstructure contribution to the very low fracture toughness of freestanding metallic thin films was investigated by bulge fracture tests on 200-nm-thick {100} single-crystalline and polycrystalline silver films. The single-crystalline films exhibited a significantly lower fracture toughness value ( K IC = 0.88 MPa m 1/2 ) than their polycrystalline counterparts ( K IC = 1.45 MPa m 1/2 ), which was rationalized by the observation of an unusual crack initiation behavior—characterized by twinning in front of the notch tip—during in situ testing in the atomic force microscope. Twinning was also observed as a dominant deformation mechanism in atomistic simulations. This twinning tendency is explained by comparing the resolved shear stresses acting on the leading partial dislocation and the full dislocation, which allows to develop a size- and orientation-dependent twinning criterion. The fracture toughness of polycrystalline samples was found to be higher because of the energy dissipation associated with full dislocation plasticity and because of crack meandering along grain boundaries.